Model Utaut Pada Perilaku Penggunaan Aplikasi Praktik Akuntansi - Nurul Nazmi; Siti Nur Azizah; Suryo Budi Santoso; Amir (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to determine the influence of UTAUT theory factors on the intentions and behavior of Accounting Practice Application users. Methodology/approach: This research uses a quantitative approach. The research data includes all accounting study program students who use the Accounting Practice Application at Muhammadiyah University Purwokerto, Wijaya Kusuma University, and Jenderal Soedirman University. Findings: The results of the significance test of performance expectations, effort expectations, social influence, facilitating conditions, and learning value have a positive effect on behavioral intentions. Behavioral intentions have a positive effect on user behavior. Practical and Theoretical Contribution/Originality: These findings contribute to researchers paying more attention to factors influencing user intentions and behavior. Research Limitation: There is data that does not meet the criteria. This causes the research results to not be able to describe the population as a whole. To overcome this obstacle, future researchers can increase the population size so that the data obtained is more representative.